La regionalización argentina como proyecto: Hipótesis del Consejo Federal de Inversiones (CFI) 1961-1965 (2019)
The following paper is focused on three regionalization projects for Argentina proposed from an institutional body such as the Federal Investment Council (IFC) between 1961 and 1965. Under the productivist development paradigm, the proposals try to spatialize the economic activity of the country from the adoption of development poles as a strategy of territorial rebalancing. However, the variables used, the methodological options and the theoretical bases are heterogeneous, resulting in three differentiated approaches. This situation is addressed as an excuse to understand the role of the IFC, its goals, actions, and actors involved.